Variación lipídica en los ovocitos de la medusa Stomolophus meleagris (Scyphozoa: Rhizostomeae), durante el desarrollo gonádico, en la laguna Las Guásimas, Sonora, México - Carvalho-Saucedo, Liliana; García-Domínguez, Federico; Rodríguez-Jaramillo, Carmen; López-Martínez, Juana (Revista de Biología Tropical, 2010)
The jellyfish Stomolophus meleagrishas potential for commercial exploitation but there is little information on their reproductive biology. This paper seeks to evaluate some biochemical and demographic characteristics of the species. Samples were taken monthly during 2005 and 2006. Jellyfish collected in 2005 were used to describe the characteristics and quantity of oocyte triglycerides and phospholipids with the Sudan black technique, and to ascertain the degree of gonadal develop-ment and sex ratio by the hematoxylin-eosin technique. The 2006 jellyfish were used to determine the size at first maturity and protein and total lipids contents. Four stages of development in both sexes were determined, with a continuous gamete development. The highest percentage of mature organisms was recorded in April. The proportion of sexes was 0.7:1.3. We found higher concentrations of triglycerides than phospholipids in the cytoplasm. There was a positive correlation between triglycerides and the diameter of the oocyte. The size at first maturity for both sexes was 105mm. The highest protein and lipids contents were obtained in April and March respectively.